Assessment of Traffic-Induced Noise Pollution in Dhaka City: A Case Study of Twenty Urban Locations - Abhijit Nath abhi; Rashedul Islam; Md. Mosfiqur Rahman Rafid; Nafi Md. Abrar Kabir (Disaster in Civil Engineering and Architecture, 2025)
This study examines the extent of noise pollution resulting from vehicular traffic across twenty strategically selected commercial and residential locations within Dhaka, Bangladesh. Data collection was conducted during afternoon peak hours (5:00 PM and 8:00 PM) using mobile-based sound meter applications in conjunction with manual classified traffic volume counts. The analysis indicates that noise levels at the majority of surveyed sites exceeded the permissible thresholds established by the World Health Organization. Notably, commercial zones exhibited particularly high average noise levels, reaching up to 76 dB(A), with Technical Mor and Mirpur-10 among the most affected areas. Although residential zones recorded comparatively lower levels, they too surpassed recommended noise standards. A strong positive correlation was identified between traffic volume and elevated sound pressure levels (SPL), emphasizing the critical need for effective urban noise mitigation measures. This paper underscores the importance of implementing updated traffic management policies, enhancing urban green infrastructure, regulating the use of vehicle horns, and fostering public awareness to address the escalating issue of traffic-induced noise pollution in Dhaka.